2019
DOI: 10.1097/mop.0000000000000714
|View full text |Cite
|
Sign up to set email alerts
|

New age technology and social media: adolescent psychosocial implications and the need for protective measures

Abstract: Purpose of review In recent years, breakthroughs and advancements in new age technology have revolutionized the way children communicate and interact with the world around them. As social media platforms such as Facebook, Instagram, and Snapchat continue to grow in popularity, their usage has raised concerns about their role and impact on adolescent development and behavior. This review examines the psychosocial implications of social media usage on youth outcomes related to body image, socializati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(23 citation statements)
references
References 50 publications
0
18
0
5
Order By: Relevance
“…For example, one item provides the following four options: "I do not feel sad" (0), "I feel sad" (1), "I am sad all the time and I can't snap out of it" (2), and "I am so sad and unhappy that I can't stand it" (3). The total possible score ranges from 0 to 63, and participants can be categorized as being at one of four levels of depression severity according to their total score: no or minimal depression (0-13), mild depression (14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe depression (≥29). The Chinese version of BDI-II was reliable on assessing depressive symptom (51).…”
Section: Depression Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, one item provides the following four options: "I do not feel sad" (0), "I feel sad" (1), "I am sad all the time and I can't snap out of it" (2), and "I am so sad and unhappy that I can't stand it" (3). The total possible score ranges from 0 to 63, and participants can be categorized as being at one of four levels of depression severity according to their total score: no or minimal depression (0-13), mild depression (14)(15)(16)(17)(18)(19), moderate depression (20)(21)(22)(23)(24)(25)(26)(27)(28), and severe depression (≥29). The Chinese version of BDI-II was reliable on assessing depressive symptom (51).…”
Section: Depression Severitymentioning
confidence: 99%
“…Beyond establishing prevalence, it is important to identify factors associated with higher and lower risk of depression among the general population during the COVID-19 pandemic. Massive social media use was found to be associated with poor sleep quality, elevated depressive symptoms, and behavior issues in adolescents, such as cyberbullying ( 15 17 ). Previous research demonstrated that greater exposure to trauma-related media information was associated with an increased risk of developing mental health problems over time.…”
Section: Introductionmentioning
confidence: 99%
“…Essas plataformas podem influenciar na autoestima do adolescente, na imagem e aceitação do próprio corpo. Muitas adolescentes são pressionadas pela sociedade a se adequarem a determinados padrões de beleza e recorrem com mais frequência a softwares de edição de imagens, o que pode aumentar a prática de cyberbullying e transtornos relacionados à imagem corporal (Kelleghan, et al, 2020;Shah et al, 2019). As adolescentes tendem a acessar a internet com mais frequência e a relatar sentimentos de solidão e desconexão social (Coughlan et al, 2021;Lupton & Deborah, 2021), em que se observa mais comportamentos de comparação com as fotos/imagens das demais colegas e mais relatos de transtornos alimentares (Lonergan et al, 2020) especialmente aquelas com transtornos psiquiátricos devido à baixa autoestima e insegurança nos relacionamentos (Durkee et al, 2012).…”
Section: Resultsunclassified
“…Os aplicativos e plataformas (YouTube, Tumblr e Instagram) geralmente atendem melhor às necessidades e mais acessados (Lupton, & Deborah, 2021). Os profissionais da saúde são incentivados a discutir e auxiliar os adolescentes sobre as questões relacionadas à imagem corporal, autoestima, pornografia e no reconhecimento de que as imagens da mídia são geralmente editadas e aprimoradas, assegurando-os sobre as consequências negativas de um uso indiscriminado desses recursos (Shah et al, 2019;Strasburger, Jordan, & Donnerstein, 2010).…”
Section: Diante Do Aumento Do Envolvimento Dos Adolescentes Com Internet O Transtorno Do Jogo Foi Incluído No Manualunclassified
See 1 more Smart Citation